Fodder shrub silage for livestock feeding systems in the high Andean tropics - Quiñones Chillambo, Juan David (2020)
In most livestock systems in the high Andean tropics of South America, there are few species of grasses to feed livestock, and the climatic variability affecting these regions means that the supply and quality of fodder for animal feed is declining. It is therefore necessary to implement supplementation strategies, with techniques such as silage, which is characterized by easy adoption among producers. The use of shrub fodder species adapted to the high Andean areas could be an alternative to store food, and be used in times of shortage, for its good contribution of biomass and nutrients. The objective of this literature review was to compile studies of nutritional quality and/or animal response, using silage from shrub fodder species in the high Andean tropics. The search for information was carried out during the months of March to May 2020, using key terms. Among the species most used to make individual and/or mixed silage were Tithonia diversifolia, Sambucus nigra, Sambucus peruviana, Smallanthus pyramidalis and Acacia decurrens, currently used in silvopastoral arrangements such as mixed fodder banks, intensive silvopastoral systems (SSPi) for direct grazing, fodder hedges and/or contour strips. In the works found, the contribution of protein, energy, minerals and high digestibility to the diet of cattle and minor species is highlighted, with improvement of productive parameters. It is concluded that, in spite of the qualities of using silage from woody fodder, the report of results in research for the high Andean tropics is still very low.